1984
DOI: 10.1002/jcp.1041210417
|View full text |Cite
|
Sign up to set email alerts
|

The role of protein phosphorylation at tyrosine in transformation and mitogenesis

Abstract: In cells transformed by avian sarcoma viruses or stimulated by growth factors, certain polypeptides become phosphorylated at tyrosine residues. It is not known if these cellular polypeptides are phosphorylated directly by the tyrosine-kinase activities which are associated with the viral transforming proteins and with growth factor receptors. It is also not clear if phosphorylation of these polypeptides is required for viral transformation or the response to growth factors. We describe here some observations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, in previous studies only the tyrosine phosphorylation of a 42-kDa protein was found to be consistently increased by many distinct mitogens, including the mitogenic protease trypsin and tumor promotors (Martin et al, 1985;Hunter and Cooper, 198513). In addition, p36, or calpactin, a peripheral membrane protein and a substrate of many transforming protein tyrosine kinases (Cooper and Hunter, 19831, was previously found to become phosphorylated on tyrosine residues in cells exposed to EGF and PDGF (Cooper and Hunter, 1983).…”
Section: Discussionmentioning
confidence: 95%
“…However, in previous studies only the tyrosine phosphorylation of a 42-kDa protein was found to be consistently increased by many distinct mitogens, including the mitogenic protease trypsin and tumor promotors (Martin et al, 1985;Hunter and Cooper, 198513). In addition, p36, or calpactin, a peripheral membrane protein and a substrate of many transforming protein tyrosine kinases (Cooper and Hunter, 19831, was previously found to become phosphorylated on tyrosine residues in cells exposed to EGF and PDGF (Cooper and Hunter, 1983).…”
Section: Discussionmentioning
confidence: 95%
“…They have important functions in the regulation of enzyme activities (19), in the initiation of protein biosynthesis (25) and in the process of cell proliferation (13,22). Besides the well studied oneogene protein kinases, a number of virus associated protein kinases has been described, not only for enveloped viruses (2,4,5,11,13), but, also for adenoviruses (1,33) and pieornaviruses (10,29).…”
Section: Introductionmentioning
confidence: 99%